Study of the work habits of the faculty of Valenzuela Municipal High School - Chico, Rosemarie A. (Parañaque City: Olivarez College, 2000)
This study aims to determine the work habits of the faculty of Valenzuela Municipal High School. Specifically, it seeks to answer the following questions: 1. What is the profile of the subjects according to sex, age, civil status and length of teaching experience. 2. What common work habits do male and female faculty members have? 3. What other work habits do male and female faculty members have? 4 What are the common work habits of faculty members with respect to age, civil status and teaching experience. 5. Is there a significant difference in the work habits of the faculty members of the Valenzuela Municipal High School according to sex, age, civil status and years of teaching experience.
Master Thesis
Keywords: Professional growth; Quality Education